Narrativas de identidade do professor de língua inglesa: o legado do Pibid - Baladeli, Ana Paula Domingos (2015)
The debate on the professional identity of teachers is directly related to teacher education, because it allows us to understand their life stories, their expectations and the main role of discourses in the process of teachers identity and difference. The conception of identity that guides this thesis is that the socially conveyed discourses on English language teachers of basic education and on the teaching profession influence the (re)construction of professional identity of pre-service teachers. The subjects of this narrative research were ten students of the Teaching Initiation Scholarship Institutional Program (Pibid) from three public universities in the state of Paraná. The aim was to identify, in the students discourses, meanings regarding the teaching profession. To achieve this goal, I based the analysis of this narrative research on the New Literacy Studies (STREET, 1995, 2014; KLEIMAN, 1995), and studies on identity (HALL, 2003, 2009; SILVA, 2009; FERREIRA, 2014). The corpus included these instruments: written autobiographical narratives, audio interviews, questionnaire, observation and field research notes from the visits in the three universities. The results indicated that participation in the Pibid program has contributed to the students professional education, the development of a teacher-researcher profile, the learning of the profession, the understanding of the teacher s role, and the understanding of the English teacher s social role. The systematic integration of the Pibid students in the school environment, in addition to the collaborative work between the university and schools, has provided meaningful teaching practices and design of teaching materials in accordance with the education official guidelines. Although the program has contributed to the discussion of the English teacher education in the contemporary context, it was possible to identify, in the Pibid students discourses, facets of identity discourse based on the family culture (hereditary facet), the belief in vocation (vocational facet), the idealized discourse (romantic facet), the highly motivating teaching practices (enthusiast facet), and, finally, the missionary belief of profession (missionary facet). In general, the Pibid program has represented an important alternative for future teachers learn the profession, but, on the other hand, it has brought to light the complexity of educating English teachers interested in working in the context of public basic education